2022
DOI: 10.3389/fonc.2022.811586
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary Lymphoid Structures and Chemokine Landscape in Virus-Positive and Virus-Negative Merkel Cell Carcinoma

Abstract: Tertiary lymphoid structures (TLSs) are used as biomarkers in many cancers for predicting the prognosis and assessing the response to immunotherapy. In Merkel cell carcinoma (MCC), TLSs have only been examined in MCPyV-positive cases. Here, we examined the prognostic value of the presence or absence of TLSs in 61 patients with MCC, including MCPyV-positive and MCPyV-negative cases. TLS-positive samples had a significantly better prognosis than TLS-negative samples. MCPyV-positive samples had a good prognosis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
(40 reference statements)
0
7
0
Order By: Relevance
“… 46 Importantly, CD4 T cells are crucial for the formation of tertiary lymphoid structures in the tumor microenvironment. 47–49 These structures of coordinated B and CD4 T cells are associated with improved survival across several cancer types including MCC 50 and likely lead to improved antitumor immunity via increased support for cancer-specific CD8 T cells. 51 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 46 Importantly, CD4 T cells are crucial for the formation of tertiary lymphoid structures in the tumor microenvironment. 47–49 These structures of coordinated B and CD4 T cells are associated with improved survival across several cancer types including MCC 50 and likely lead to improved antitumor immunity via increased support for cancer-specific CD8 T cells. 51 …”
Section: Discussionmentioning
confidence: 99%
“…46 Importantly, CD4 T cells are crucial for the formation of tertiary lymphoid structures in the tumor microenvironment. [47][48][49] These structures of coordinated B and CD4 T cells are associated with improved survival across several cancer types including MCC 50 and likely lead to improved antitumor immunity via increased support for cancer-specific CD8 T cells. 51 To determine which of many roles neoantigenspecific CD4 T cells were playing in this patient's clinical response, we phenotyped these cells via scRNAseq (figures 3B and 4A).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, they observed that TLS were significantly associated with higher CD8:CD4 T-cell ratio in the tumor periphery, but not within the tumor center [ 102 ]. Recently, Nakamura et al examined both virus-positive and negative cases and determined that there are five chemokine genes— CCL5 , CCR2 , CCR7 , CXCL9 , and CXCL13 —with significantly higher expressions in TLS-positive samples compared to TLS-negative samples [ 103 ]. Regardless of the expression of TLS in MCPyV-positive tissue samples, virus-positive tissue samples had a similar prognosis.…”
Section: Formation Of Tertiary Lymphoid Structuresmentioning
confidence: 99%
“…Interestingly, the chemokine genes CXCL10 and CX3CR1 had different expression levels in the presence of MCPyV infection (compared to lack of infection) in TLS-negative samples. It was also shown that patients with high CXCL13 or CCL5 expression had better prognosis compared to those with lower expression, suggesting that chemokine expression profiles may offer insights into the TME and thereby may represent a potential prognostic marker [ 103 ].…”
Section: Formation Of Tertiary Lymphoid Structuresmentioning
confidence: 99%
“…Although spontaneous regression is thought to occur as a result of the high immune activity of MCC, 3,4 the tumour immune microenvironment has not been analysed in detail. We previously analysed tumour immune activity in 41 samples by comprehensive RNA sequencing using a next‐generation sequencer, 5 and the presence of tertiary lymphoid structures (TLS) in 61 cases of MCC 6 . As a result, MCC can be divided into groups with high‐ and low‐immune activity, 5 MCPyV‐positive cases had a good prognosis with or without TLS, MCPyV‐negative, TLS‐positive cases had a good prognosis comparable to MCPyV‐positive cases, and MCPyV‐negative and TLS‐negative cases had a worse prognosis than the other cases 6 .…”
Section: Introductionmentioning
confidence: 99%